Development and validation of a formula for objective assessment of cervical vertebral bone age - Chandrasekar, Raghavan; Chandrasekhar, Shyamala; Sundari, K. K. Shantha; Ravi, Poornima (Progress in orthodontics, 2020)
Background and aim Determination of skeletal maturity and bone age from cervical vertebrae has been well documented. Most methods described use subjective evaluation of morphological characteristics of cervical vertebrae and may be prone to variability and error. A few objective methods have also been developed, specific for certain populations and genders. The aim of this study was to establish and validate an objective method to determine cervical vertebral bone age from lateral cephalometric radiographs, for Asian South Indian patients of both genders. Methods Ninety boys and 90 girls between 9 and 15 years of age were recruited, and their lateral cephalograms were taken. Using measurements made from the third and fourth cervical vertebrae, a formula to determine cervical vertebral bone age was derived using stepwise regression analysis. To validate the formula, a separate sample of 30 boys and 30 girls was chosen, and hand-wrist radiographs and lateral cephalograms were obtained. Cervical vertebral bone age (CVBA) was determined by applying the formula derived. Bone age was also calculated using the Tanner-Whitehouse 3 method. The bone ages determined by both methods were compared to each other and chronological age, using one-way ANOVA, Tukey’s post hoc analysis, and Pearson’s correlation coefficient. Results The formulae derived in the current study to determine CVBA differed for both genders. No statistically significant difference was found between CVBA, bone age derived by the Tanner-Whitehouse 3 method, and chronological age for both boys ( p value = 0.425) and girls ( p value = 0.995). A moderate to strong positive correlation was found between CVBA, bone age, and chronological age. Conclusion The formulae derived in this study were validated and are reliable for objectively determining cervical vertebral bone age and skeletal maturation from lateral cephalograms for Asian South Indian patients of both genders.